2013
DOI: 10.1007/s10195-013-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance arthrography for femoroacetabular impingement surgery: is it reliable?

Abstract: BackgroundMagnetic resonance arthrography (MRA) is commonly used to demonstrate injury to the labrum and hyaline cartilage in patients with femoroacetabular impingement (FAI). The purpose of this study was to assess the diagnostic correlation between MRA and findings at arthroscopic and open surgery.Materials and methodsMRA reports of 41 hips with symptomatic FAI were reviewed and compared with subsequent intraoperative findings (n = 21 surgical dislocations and n = 20 therapeutic hip arthroscopies). Each case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…Four studies (n=188 participants)65 68 79 81 investigated the use of the FADDIR test with MR angiogram (MRA) reference standard, four studies (n=319 participants)68 69 71 76 investigated the use of the FADDIR test with surgery reference standard, and two studies (n=27 participants)63 74 investigated the use of the Flex IR test with surgery reference standard.…”
Section: Meta-analysismentioning
confidence: 99%
“…Four studies (n=188 participants)65 68 79 81 investigated the use of the FADDIR test with MR angiogram (MRA) reference standard, four studies (n=319 participants)68 69 71 76 investigated the use of the FADDIR test with surgery reference standard, and two studies (n=27 participants)63 74 investigated the use of the Flex IR test with surgery reference standard.…”
Section: Meta-analysismentioning
confidence: 99%
“…Because we performed a resection to bone, it is difficult to compare our results with other studies where the amount of resection is unspecified [1,3,5,6,11,18,29,34,38,53] and was probably limited to partial débridement in many cases. We attempt to repair most labral tears, but the patients here had no option other than reconstruction with a graft, a procedure we had not adopted at the time.…”
Section: Discussionmentioning
confidence: 99%
“…Abrams et al [1] found a positive relationship between age and the presence of ''inhomogeneous regrowth'' of the labrum, and the average age of their subjects was 29 years. The condition of the labrum after various hip preservation procedures has been examined by arthroscopy [1,18,29,34,53], MRA [3,5,11,18], and during open procedures [6,38]. Overall, these reports contain only limited information on the extent of the initial labral resection.…”
Section: Discussion Of Imagingmentioning
confidence: 99%
“…Magnetic resonance imaging is especially useful in the evaluation of avascular necrosis, a cause of symptoms, as well as in the evaluation of femoral neck stress fractures, 21 whereas MRA may be most helpful in the evaluation of labral tears, cam-type lesions, and os acetabula, with a sensitivity and specificity for detecting labral tears of 81% and 51%, respectively. 45 It should be noted, however, that for patients for whom the physician has an already high clinical suspicion of labral pathology, MRA has a poor negative predictive value and thus is unhelpful in ruling out labral lesions. 46 Imaging findings may be helpful in preoperative planning, especially with regard to determining the need for labral repair and potential femoral head or acetabular microfracture.…”
Section: Advanced Imagingmentioning
confidence: 98%